Outcomes of Venous End‐to‐Side Microvascular Anastomoses of the Head and Neck. (19th October 2020) - Stewart, Matthew; Hammond, Perry; Khatiwala, Ishani; Swendseid, Brian; Taghizadeh, Farshid; Petrisor, Daniel; Zhan, Tingting; Goldman, Richard; Luginbuhl, Adam; Heffelfinger, Ryan; Sweeny, Larissa; Wax, Mark K.; et al.
Abstract : Objectives/Hypothesis: The literature on outcomes of end‐to‐side (ETS) anastomoses for microvascular reconstruction of the head and neck is limited. This series reviews ETS in free tissue transfer (FTT) across multiple institutions to better understand their usage and associated outcomes. Study Design: Retrospective review of 2482 consecutive patients across three tertiary institutions. Methods: Adult patients (> 18) who received a FTT from 2006 to 2019 were included. Results: Two hundred and twenty‐one FTT were identified as requiring at least one ETS anastomosis. These ETS cases had a failure rate of 11.2% in comparison to 3.8% in a cohort of end‐to‐end (ETE) cases ( P < .001). ETS cases were significantly more likely to have a prior neck dissection ( P < .001), suggesting the ETS method was utilized in select circumstances. A second ETS anastomosis improved survival of the FTT ( P = .006), as did utilization of a coupler over suture ( P = .002). Failure due to venous thrombosis was significantly more common with one ETS anastomosis instead of two ETS anastomoses ( P = .042). Conclusions: ETS is effective but is often used as a secondary technique when ETE is not feasible; as such, in this series, ETS was associated with higher failure. A second anastomosis and the use of the coupler for completing the anastomoses were associated with lower rates of failure. Level of Evidence: 3 Laryngoscope, 131:1286–1290, 2021